Aeroengine High-Attitude/Low Mach Number Oscillations: Mechanism and Prevention Design - Jiqiang Wang (International Journal of Aerospace Engineering)
The issue of aeroengine oscillations over high-attitude and low-speed flight envelope has been an unsolved problem due to their classified nature and hard reproduction in simulated altitude test stand. Efforts have been sought for either structural integrity or component damage. However, it is rarely realized that the oscillations can be an inherent property of the engine itself. Consequently, a dynamical system approach is proposed in this paper to demonstrate that engine oscillations are recurring over high-attitude and low-speed flight envelope, yet they can be suppressed through appropriate control designs. However, the resulting design can be compromised with the conventional high-gain control where the transient and steady-state performance must be balanced with disturbance attenuation performance. Examples are given to illustrate and validate the claims made through the en route analysis.